Study of Agricultural Market in India with Illustration of Business Opportunity - Patil, Tushar; Joshi, Saurabh Arvind; Bhatia, Dipti Kiran; Rajendran, Santosh (2010)
The role of agriculture in India has been not just to produce food but to sustain and contribute towards overall socio-economic development in rural societies. Overregulation of agriculture along with lack of infrastructural facilities and small fragmented unproductive landholdings has increased costs, price risks and uncertainty. The agricultural system has traditionally been unfair to farmers as well as the end consumers. This study will analyze the agricultural marketing system in India from the perspective of issues faced by farmers, traders and food processors. These issues include information asymmetry, excessive margins in price at each level of the supply chain, limited reach of technology in rural India, post harvest wastage etc. It has also been characterised by lack of infrastructure, inadequate marketing channels to the farmers and archaic government policies that prevented investment into this sector for a long time. Indian agriculture has changed a lot in past few years, but still not kept the pace due to existence of these issues. The presence of these issues in Indian agricultural market is rather undeveloped and inefficient characterised by a long supply chain, lack of transparency on pricing and quality issues. The purpose of this report is to analyse these challenges and opportunities while providing recommendations from the agribusiness perspective. Price variations and availability of the produce in the market is analysed with the help of surveys, interviews and latest price data available on the web-portals. This report also highlights the initiatives taken by two firms (PepsiCo and ITC eChoupal) for empowering farmers and shortening the long supply chain for marketing agricultural produce. It sets out the scope, proposed objectives and initial research of information for understanding the potential synergies in context with the Indian agricultural market.